2009
DOI: 10.1007/s12016-009-8117-2
|View full text |Cite
|
Sign up to set email alerts
|

A Cellular Viewpoint of Anti-FVIII Immune Response in Hemophilia A

Abstract: A large proportion of hemophilia A patients who receive replacement therapy, develop an immune response toward the infused factor VIII (FVIII). In this review, we discuss recent progress in several aspects of the anti-FVIII immune response, focusing on the sites of FVIII endocytosis (marginal zone of the spleen and bleeding site), the type of antigen-presenting cells (dendritic cells, macrophages and B cells) and endocytic receptors, implicated in FVIII presentation to T cells during primary and secondary immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 84 publications
0
31
0
Order By: Relevance
“…S1B) showed reduction (not significant) in the effector T cell populations in mice receiving cytokineconditioned DCs versus mice receiving control DCs, but at levels similar to those in OVA-only mice. Blood-borne antigens are filtered by the spleen, which provides the ideal environment for initiation and amplification of the immune responses (Lacroix-Desmazes et al, 2008;Andre et al, 2009). Mice were killed 1 week after the second OVA challenge (week 6), and splenocytes were analyzed ex vivo.…”
Section: Tgf-b 1 And/or Il-10-conditioned Dcs Do Not Reduce Activatedmentioning
confidence: 99%
See 2 more Smart Citations
“…S1B) showed reduction (not significant) in the effector T cell populations in mice receiving cytokineconditioned DCs versus mice receiving control DCs, but at levels similar to those in OVA-only mice. Blood-borne antigens are filtered by the spleen, which provides the ideal environment for initiation and amplification of the immune responses (Lacroix-Desmazes et al, 2008;Andre et al, 2009). Mice were killed 1 week after the second OVA challenge (week 6), and splenocytes were analyzed ex vivo.…”
Section: Tgf-b 1 And/or Il-10-conditioned Dcs Do Not Reduce Activatedmentioning
confidence: 99%
“…Normally, when therapeutic proteins are administered intravenously, antigen presentation is expected to take place largely in the spleen (Andre et al, 2009;Waters and Lillicrap, 2009). In the marginal zone of the spleen, antigen is endocytosed and processed by antigen-presenting cells (APCs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the severity of the F8 gene mutation has the greatest influence on a patient's risk for developing inhibitors. Patients with large deletions, nonsense mutations, and chromosomal inversions have the highest incidence of severe inhibitor formation [26]. Further experimental evidence for the necessity of FVIII expression during lymphocyte development was provided by gene therapy studies in animal models that showed that stable expression of FVIII protein in thymus or bone marrow correlated with tolerance to FVIII [27,28].…”
Section: Anti-fviii Antibody Response-a Break In Tolerancementioning
confidence: 99%
“…[6][7][8][9][10] Binding of antigenic peptides to a particular MHCII is dictated by polymorphisms in 4 or 5 major pockets within its peptide-binding groove. Peptide side chains at relative "anchor" positions 1, 4, 6, 7, and 9 bind to these pockets, with size, shape, and charge or hydrophobic complementarity determining their affinity.…”
Section: Introductionmentioning
confidence: 99%